An improved technique of competence analysis for occupational standard development - Petai Chuaphun (2019)
© 2018 IEEE. The occupational standard is a benchmark for developing the workforce skills of citizens to meet the industrial requirements. This standard is normally developed from the industry section according to the real activities taking place in the workplace. Generally, it is developed by utilized Functional Analysis to construct a list of competencies for each occupation. However, it becomes a complex task for the large-scale industry, which consists of a large number of occupations. The complication and time consumption are significant issues associated with the incomplete information. To overcome these problems, an improved technique by utilizing Functional Analysis with DACUM is proposed. The experiment result shows that the proposed technique can provide the better result of the occupational standard than that of the occupational standard by using only Functional Analysis. Furthermore, it is a suitable tool for analyzing a large scale industry as well as giving a clear picture of occupations to derive the competencies.